Analisis Penegakan Hukum Terhadap Pelanggaran Protokol Kesehatan Berdasarkan Asas Persamaan Didepan Hukum - Desi Yana S; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
To minimize the spread of Covid-19 in Indonesia, a Health Protocol has been implemented.However, the infection rate continued to increase until it spread throughout Indonesia. This happensbecause there are still many violations of the Health Protocol, especially not wearing masks andkeeping a safe distance. Lack of public awareness of the importance of maintaining health is a factorcausing an increase in cases. As well as in the law enforcement process, health protocol violations areconsidered to have occurred selectively in the application of the law by law enforcers, such as in thecase of Rizieq Sihab when he held his daughter's wedding compared to Atta Halilintar's wedding andviolations committed by state officials where no legal action was taken. So it tends to result in peoplenot taking their health seriously and complying with the rules. This makes the law in Indonesia doesnot put forward the principle of equality before the law which is the basis that all are treated the same,there is no difference before the law.The type of research used is normative legal research, which is research conducted byexamining secondary data or research based on standard rules that have been recorded, called libraryresearch. This research is descriptive in nature, namely a study that aims to make a clear and detaileddescription of the problem.The results of this study are the process of law enforcement against health protocol violations,namely applying Article 93 of Law No. 6 of 2018 for those who violate it by imposing a 1 year prisonsentence and a 100 million fine, but it is still not running optimally and does not reflect equality beforethe law. There is a disparity in legal treatment of fellow violators and the attitude of selective loggingby law enforcement officials both in imposing sanctions and not taking action against officials whoviolate the health protocol. when compared to other countries' health protocol law enforcement, thesanctions are quite heavy but effective and the apparatus has strong firmness. So the law enforcementprocess should have strong integrity from law enforcement officials in enforcing the law in the midst ofsociety. As well as the need for additional studies in Law No. 6 of 2018 concerning health protocolsnot wearing masks, maintaining distance, avoiding crowds so that there are no multipleinterpretations and the proper application of articles to actions so that justice can be properly realizedand applies equally to all Indonesian people.Keywords: Health protocol, Law Enforcement, Equality Before the Law